Robustness of Equilibrium Exchange Rate Calculations to Alternative Assumptions and Methodologies - Clark, Peter (IMF Working Papers; Working Paper, 1994)
This paper explores a number of methodological issues that arise in the calculation of equilibrium exchange rates, which are identified in this paper as those real effective exchange rates consistent with macroeconomic equilibrium, id est, internal and external balance. A partial equilibrium, comparative static analysis is presented and the methodology is applied to the break-up of the Bretton Woods exchange rate system. Then the dynamic interaction between the current account and the stock of net foreign assets is examined. Finally, the analysis uses a more general equilibrium approach by relying on simulations using MULTIMOD, a multicountry econometric model. The paper demonstrates the extent to which the equilibrium exchange rate calculations depend upon alternative assumptions regarding factors that affect internal and external balance. In addition, results obtained using the comparative static and dynamic macroeconomic approaches are compared.